2018
DOI: 10.1016/j.envpol.2018.08.077
|View full text |Cite
|
Sign up to set email alerts
|

Mytilus spp. as sentinels for monitoring microplastic pollution in Norwegian coastal waters: A qualitative and quantitative study

Abstract: Microplastic (MP) contamination is ubiquitous in the environment and many species worldwide have been shown to contain MP. The ecological impact of MP pollution is still unknown, thus there is an urgent need for more knowledge. One key task is to identify species suitable as sentinels for monitoring in key eco-compartments, such as coastal waters. In Norway, mussels (Mytilus spp.) have been monitored for hazardous contaminants through OSPAR since 1981. Norway has the longest coastline in Europe and adding MP t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
2
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(108 citation statements)
references
References 54 publications
3
74
2
5
Order By: Relevance
“…So far, however, presence of fibers was reported in various species of seafood (Rochman et al, 2015). Blue mussels were examined for their suitability to monitor microplastic pollution in Norwegian coastal waters where mussels contained on average 1.5 microplastics per individual (Bråte et al, 2018). Overall, 83% of the particles investigated in that study were fibers.…”
Section: Introductionmentioning
confidence: 99%
“…So far, however, presence of fibers was reported in various species of seafood (Rochman et al, 2015). Blue mussels were examined for their suitability to monitor microplastic pollution in Norwegian coastal waters where mussels contained on average 1.5 microplastics per individual (Bråte et al, 2018). Overall, 83% of the particles investigated in that study were fibers.…”
Section: Introductionmentioning
confidence: 99%
“…MPs are considered an emerging pollutant 3 because they have strong abilities to become enriched in heavy metals 4,5 and persistent organic pollutants (POPs) 6,7 and can affect the growth of organisms 8 . Since 2013, extensive data have been accumulated on the spatial distribution of MPs in coastal areas 9,10 , oceans 11,12 , rivers 13,14 , lakes 15,16 , sediments 17,18 and soil 19,20 . MPs have been found in remote areas 21,22 , which confirmed that MPs could be transported over long distances via the atmosphere 21 and ocean currents 12,15 , which makes MPs an extensive global pollutant.…”
mentioning
confidence: 99%
“…Samples were not processed inside a clean air device (Wesch et al, 2017). To apply this workflow to environmental samples, it is recommended to follow established QA/QC method, such as those described in Karami et al (2017), Bråte et al (2018), or Hermsen et al (2018.…”
Section: Yesmentioning
confidence: 99%